Astute competition the economics of strategic diversity - Johnson, Peter, 1956- (Technology, innovation, entrepreneurship, and competitive strategy series., 2007)
The first part of this book aims to provide a rigorous account of the five key strategic building blocks that underpin an analysis of heterogeneous competition. The second part deals with how these strategic concepts, embedded in various analytical techniques and tools, can illuminate strategy practice.